Exploring the Impact of Artificial Intelligence (AI) Tools in Providing Writing Feedback for EFL Learners - Shevanya Natalie (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2025)
This study explores the perceptions of EFL students regarding the use of AI-powered tools, such as Grammarly and ChatGPT, in enhancing their academic writing skills. Employing Davis’s Technology Acceptance Model (TAM) as a theoretical framework, the research examines three primary dimensions: perceived usefulness (PU), perceived ease of use (PEOU), and AI vs Human Feedback. Six undergraduate students from a university in Indonesia participated in semi-structured interviews, which were analyzed using thematic analysis. Findings indicate that students value AI tools for their real-time, grammar-focused feedback, which improves coherence, clarity, and writing efficiency. However, students often preferred human feedback for its contextual depth and personalized nature, especially for complex tasks. While AI tools were praised for their accessibility and time-saving features, their inability to fully capture individual writing styles and contexts highlighted the need for a hybrid feedback approach. This study suggests combining AI and human feedback to provide comprehensive support, balancing technical accuracy with nuanced developmental guidance, thus fostering enhanced learning experiences for EFL learners